Optical Sensors New Developments and Practical Applications - Yasin, Mohamad; Wadi Harun, Sulaiman; Arof, Hamzah (IntechOpen, 2014)
This book is a compilation of works presenting recent developments and practical applications in optical sensor technology. It contains 10 chapters that encompass contributions from various individuals and research groups working in the area of optical sensing. It provides the reader with a broad overview and sampling of the innovative research on optical sensors in the world.